Bovine Papillomavirus Type 2 (BPV-2) E5 Oncoprotein Binds to the Subunit D of the V(1)-ATPase Proton Pump in Naturally Occurring Urothelial Tumors of the Urinary Bladder of Cattle - Roperto, Sante (Public Library of Science, 2014)
BACKGROUND: Active infection by bovine papillomavirus type 2 (BPV-2) was documented for fifteen urinary bladder tumors in cattle. Two were diagnosed as papillary urothelial neoplasm of low malignant potential (PUNLMP), nine as papillary and four as invasive urothelial cancers. METHODS AND FINDINGS: In all cancer samples, PCR analysis revealed a BPV-2-specific 503 bp DNA fragment. E5 protein, the major oncoprotein of the virus, was shown both by immunoprecipitation and immunohistochemical analysis. E5 was found to bind to the activated (phosphorylated) form of the platelet derived growth factor β receptor. PDGFβR immunoprecipitation from bladder tumor samples and from normal bladder tissue used as control revealed a protein band which was present in the pull-down from bladder cancer samples only. The protein was identified with mass spectrometry as “V(1)-ATPase subunit D”, a component of the central stalk of the V(1)-ATPase vacuolar pump. The subunit D was confirmed in this complex by coimmunoprecipitation investigations and it was found to colocalize with the receptor. The subunit D was also shown to be overexpressed by Western blot, RT-PCR and immunofluorescence analyses. Immunoprecipitation and immunofluorescence also revealed that E5 oncoprotein was bound to the subunit D. CONCLUSION: For the first time, a tri-component complex composed of E5/PDGFβR/subunit D has been documented in vivo. Previous in vitro studies have shown that the BPV-2 E5 oncoprotein binds to the proteolipid c ring of the V(0)-ATPase sector. We suggest that the E5/PDGFβR/subunit D complex may perturb proteostasis, organelle and cytosol homeostasis, which can result in altered protein degradation and in autophagic responses.